Изменение параметров морфогенеза Arabidopsis thaliana L. при хроническом облучении семян и проростков малыми дозами редкоионизирующей радиации - Литвинов, С.В.; Рашидов, Н.М. (Фактори експериментальної еволюції організмів, 2016)
Aim. Our purpose was to evaluate influence of small doses of ionizing radiation on the growth and development of the model plant A. thaliana L., irradiated at the stage of dry seeds or seedlings. Methods. In our experiments we studied the morphometric parameters of Arabidopsis and the correlation between them during the process of growth and development in post-radiation period until the end of the vegetation and plant death. Results. We have confirmed both effect of root growth stimulation in chronically irradiated seedlings and accelerated flowering combined with shortening of vegetative period in plants which were grown from irradiated seeds. Conclusions. Chronic exposure of seeds to low doses of ionizing radiation induces the appearance of plants with an abnormal phenotype and also modifies correlative relationships between morphometric parameters of developing plants. Keywords: Arabidopsis thaliana L., ionizing radiation, low doses, chronic exposure, plant development.